2003
DOI: 10.1161/01.cir.0000057545.82749.ff
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Janus Kinase (JAK)-Signal Transducers and Activators of Transcription (STAT) Signaling in Patients With End-Stage Dilated Cardiomyopathy

Abstract: Background-Experimental studies indicate that interleukin-6 (IL-6)-related cytokines, signaling via the shared receptor gp130, Janus kinases (JAKs), and signal transducers and activators of transcription (STATs), provide a critical cardiomyocyte survival pathway in vivo. Little is known about the activation of this signaling pathway in the myocardia of patients with end-stage dilated cardiomyopathy (DCM). Methods and Results-We performed a comprehensive expression and activation analysis of IL-6 -related cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
103
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 22 publications
12
103
0
1
Order By: Relevance
“…Not much information is available to date on the expression state of SOCS proteins, negative regulators of gp130-JAK/STAT signaling, in human failing hearts. One report shows that terminally failing human hearts display increased SOCS-1 and reduced SOCS-3 protein levels [113]. Taken together, circulating IL-6 cytokines positively correlate with the progression of heart failure and the local IL-6-gp130-STAT3 signaling cascade in human failing hearts is dysregulated at all levels.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 95%
See 2 more Smart Citations
“…Not much information is available to date on the expression state of SOCS proteins, negative regulators of gp130-JAK/STAT signaling, in human failing hearts. One report shows that terminally failing human hearts display increased SOCS-1 and reduced SOCS-3 protein levels [113]. Taken together, circulating IL-6 cytokines positively correlate with the progression of heart failure and the local IL-6-gp130-STAT3 signaling cascade in human failing hearts is dysregulated at all levels.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 95%
“…■ Changes in myocardial expression of the IL-6 type family of cytokines Intriguingly, not only systemic levels of IL-6 type cytokines and sgp130 are elevated in cardiovascular disease but also the local gp130-STAT3 signaling cascade is altered at every level in the failing human heart [28, 67,68,113,175]. For instance, it is known that both CT-1 and LIF are increasingly expressed in the failing left ventricular myocardium.…”
Section: General Overview On Gp130 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ligand-binding IL-6R alone is not capable of signal transduction, the signaling component gp130 is also involved in the transduction of signals from other ligands of the IL-6 family. When IL-6 is induced by sustained β-adrenoceptor activation, the capacity for signal transduction by IL-6 is probably maintained, because: (a) we found no lowering in the myocardial mRNA expression of IL-6R or gp130 in any model with sustained β-adrenergic activation; (b) in cardiomyocytes, isoproterenol causes a delayed activation of STAT3 (a hallmark of gp130-dependent signal transduction), which can be attenuated by an IL-6-neutralizing antibody (6); and (c) in failing human myocardium, other studies have demonstrated phosphorylation of gp130 and of downstream signaling components (STAT1, STAT3) (24,25).…”
Section: Relevance Of β-Adrenoceptor-mediatedmentioning
confidence: 99%
“…STAT3 in particular mediates a signal transduction that promotes cellular growth and reverses apoptosis, and thus plays a key role in neovascularization and cellular survival. Studies have shown that deletion of STAT3 in mice causes cardiomyopathy (14), and in patients with the disease, the level of STAT3 in the myocardia was significantly low (15). All these suggest that activating the JAK/STAT3 pathway may be the key to preventing the onset of heart failure.…”
Section: Discussionmentioning
confidence: 98%